Respuesta :

Answer:

[tex] \red{ \bold{\frac{2x(x - 1) + 3(2x - 3)}{(2x + 3)(2x - 3)(x - 1)} }}[/tex]

Step-by-step explanation:

[tex] \frac{2x}{4 {x}^{2} - 9 } + \frac{3}{2 {x}^{2} + x - 3} \\ \\ = \frac{2x}{(2 {x})^{2} - {(3)}^{2} } + \frac{3}{2 {x}^{2} - 2x + 3x - 3} \\ \\ = \frac{2x}{(2x + 3)(2x - 3)} + \frac{3}{2 {x}(x - 1) + 3(x - 1)} \\ \\ = \frac{2x}{(2x + 3)(2x - 3)} + \frac{3}{(x - 1) (2x + 3)} \\ \\ = \frac{2x(x - 1)}{(2x + 3)(2x - 3)(x - 1)} + \frac{3(2x - 3)}{(x - 1) (2x + 3)(2x - 3)} \\ \\ \purple{ \bold{ = \frac{2x(x - 1) + 3(2x - 3)}{(2x + 3)(2x - 3)(x - 1)} }}[/tex]

ACCESS MORE